CRISPR/Cas9-Mediated Mutagenesis of Four Putative Symbiosis Genes of the Tropical Tree Parasponia andersonii Reveals Novel Phenotypes - van Zeijl, Arjan; Wardhani, Titis A. K.; Seifi Kalhor, Maryam; Rutten, Luuk; Bu, Fengjiao; Hartog, Marijke; Linders, Sidney; Fedorova, Elena E.; Bisseling, Ton; Kohlen, Wouter; Geurts, Rene (Frontiers in Plant Science, 2018)
Parasponia represents five fast-growing tropical tree species in the Cannabeaceae and is the only plant lineage besides legumes that can establish nitrogen-fixing nodules with rhizobium. Comparative analyses between legumes and Parasponia allows identification of conserved genetic networks controlling this symbiosis. However, such studies are hampered due to the absence of powerful reverse genetic tools for Parasponia. Here, we present a fast and efficient protocol for Agrobacterium tumefaciens-mediated transformation and CRISPR/Cas9 mutagenesis of Parasponia andersonii. Using this protocol, knock-out mutants are obtained within three months. Due to efficient micro-propagation, bi-allelic mutants can be studied in the T0 generation, allowing phenotypic evaluation within six months after transformation. We mutated four genes - PanHK4, PanEIN2, PanNSP1, and PanNSP2 - that control cytokinin, ethylene or strigolactone hormonal networks and that in legumes commit essential symbiotic functions. Knockout mutants in Panhk4 and Panein2 displayed developmental phenotypes, namely reduced procambium activity in Panhk4 and disturbed sex differentiation in Panein2 mutants. The symbiotic phenotypes of Panhk4 and Panein2 mutant lines differ from those in legumes. In contrast, PanNSP1 and PanNSP2 are essential for nodule formation, a phenotype similar as reported for legumes. This indicates a conserved role for these GRAS-type transcriptional regulators in rhizobium symbiosis, illustrating the value of Parasponia trees as a research model for reverse genetic studies.